Relationship of Cyclin D1 expression, Estrogen Receptor status and Histological grading in Invasive Duct Carcinoma of the breast - Sanda, Aung; Aye Aye , Thike; Tha, Aung (Myanmar Health Science Journals, 2011)
Invasive duct carcinoma of the breast is a clinically and biologically heterogeneous disease. Histological grading was done according to Modified Bloom and Richardson Grading in 40 cases of formalin fixed, paraffin embedded tissue sections of Invasive duct carcinoma (NST). Estrogen receptor (ER) status and Cyclin D1 expression were detected by standard immunohistochemistry. Cyclin D1 expression was detected in 43% (17 of 40) of cases, and was inversely associated (x2 test) with histological grade (p=0.01). ER immunoreactivity was found in 30% (12 of 40) of patients and was inversely associated with histological grade (p=0.021). Cyclin D1 immunoreactivity was positively associated with estrogen receptor expression (p=0.043). There was no significant correlation with clinical prognostic parameters of age, menopausal status, tumour size and clinical stage.